Unraveling the mosaic of emerging nosocomial infections: Revealing insights from two cases of Ochrobactrum anthropi bacteremia - Khan, Moiz Ahmed; Khursheed, Nazia; Adnan, Fareeha; Zahid, Qurat-ul-Ain (Infectious Diseases Journal of Pakistan, 2025)
Ochrobactrum anthropi with its strong survival ability and subtle clinical presentation, has been associated with hospital-acquired infections in immunocompromised patients. Lack of knowledge regarding its clinical importance is the prime reason for underreporting of cases. We present here two cases of Ochrobactrum anthropi bacteremia in nephrology and oncology patients, suggesting that these infections may be fairly common in immunocompromised individuals. No antimicrobial resistance was observed in our first case and the patient responded to monotherapy with meropenem whereas, the second case involved infection with a multidrug resistant strain of Ochrobactrum anthropi and improved with combination therapy comprising of levofloxacin and trimethoprim-sulfamethoxazole. To ensure that such pathogens are not missed, more thorough and accurate diagnostic procedures must be employed. A favorable outcome in such cases can be possible with prompt identification and optimal antibiotic therapy. Keywords: Ochrobactrum anthropi, Nephrology, Oncology, Immunocompromised, Bacteremia